2001
DOI: 10.1164/ajrccm.164.5.2007060
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Hypercapnic Acidosis on Ventilator-induced Lung Injury

Abstract: To investigate whether respiratory acidosis modulates ventilator-induced lung injury (VILI), we perfused (constant flow) 21 isolated sets of normal rabbit lungs, ventilated them for 20 min (pressure controlled ventilation [PCV] = 15 cm H(2)O) (Baseline) with an inspired CO(2) fraction adjusted for the partial pressure of CO(2) in the perfusate (PCO(2) approximately equal to 40 mm Hg), and then randomized them into three groups. Group A (control: n = 7) was ventilated with PCV = 15 cm H(2)O for three consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 24 publications
7
124
0
8
Order By: Relevance
“…Our results confirm earlier reports from other injury models, that CO 2 influences vascular barrier function and thereby the mechanics of the injured lung (4)(5)(6)(7)(8)(9). However, we also show that CO 2 tension influences the probability that injured cells will repair plasma membrane defects.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm earlier reports from other injury models, that CO 2 influences vascular barrier function and thereby the mechanics of the injured lung (4)(5)(6)(7)(8)(9). However, we also show that CO 2 tension influences the probability that injured cells will repair plasma membrane defects.…”
supporting
confidence: 92%
“…Concern about detrimental effects of acidemia on renal and cardiovascular function have motivated attempts to enhance CO 2 removal by tracheal gas insufflation (2) and have led to unsubstantiated recommendations about the use of bicarbonate buffers in hypercapnic patients (3). More recent data suggest that hypercapnia may actually protect the lung from certain manifestations of ischemiareperfusion, endotoxin, and mechanical ventilation-related injury (4)(5)(6)(7)(8)(9). Hypocapnia, in contrast, and correction of acidemia may be harmful (10)(11)(12).…”
mentioning
confidence: 99%
“…Although a lot of evidence suggests that hypercapnic acidosis has a valuable role in experimental models, 14,15,18,37,45 we also should pay attention to consider harmful effects of hypercapnia and/or acidosis on its potential clinical application. It is clear that hypercapnic acidosis may exert adverse hemodynamic effects in patients Histogram of early apoptosis and late apoptosis/necrosis in the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated hypercapnia's protective effects against VILI in both isolated perfused lungs and an animal model. [14][15][16] The mechanism by which hypercapnic acidosis affects acute lung injury, includes the attenuation of NF-kB activation, 17 the inhibition of endogenous xanthine oxidase 18 and oxygen radical formation, 19 and the reducing release of the cytokines. 12,20,21 However, it is still unclear whether hypercapnic acidosis may affect cell apoptosis and oxidative stress injury of the alveolar by MAPK pathways in VILI.…”
Section: Introductionmentioning
confidence: 99%
“…29 The pathway leading to endocytosis is triggered by the intracellular increase of Ca 2+ , leading to an activation of Ca 2+ -calmodulin dependent kinase kinase-b, which phosphorylates the have shown that elevating CO 2 levels up to 100 mmHg (known as "permissive hypercapnia," "corrective hypercapnia," or "protective hypercapnia") exerts important protective effects on lungs and helps reduce ventilator-induced ALI. [13][14][15][16][17][18][19][20][21] According to these studies, hypercapnic acidosis can reduce alveolar oxygen tension and intrapulmonary shunts. In addition, it shifts the hemoglobin oxygen dissociation curve to the right, thus improving arterial oxygenation.…”
Section: Pathophysiological Effects and Molecular Responses To Hypercmentioning
confidence: 99%